Inflation, Devaluation And Struggle Of Social Groups In Latin America - Schuldt, Jurgen (Universidad del Pacífico, 1973)
This article is a critique of the most important authors who studied the causes of inflation a decade ago: the monetarists and the structuralists. After an epoch of intense debate it followed one of scientific sterility, without a real discussion of the real causes. The goal is to understand the causes of inflation and deflation in Latin America, pointing out the importance of social groups as a source of inflation.